The Red River Hill - Balcomb, Kenneth C. frey50 (Albuquerque, NM Albuquerque HIstorical Society, 1981)
The author tells of building a road over the pass at Red River in the days when adequate roads for automobiles were at a premium.
#1
Keywords: New Mexico - Northeastern New Mexico and Southeastern Colorado; Red River - New Mexico. -- Engineering - Roads